PENINGKATAN SUHU KRITIS PADA SINTESIS BAHAN SUPERKONDUKTOR MAGNESIUM DIBORIDA DENGAN VARIASI UKURAN PARTIKEL SERBUK MG - Herbirowo, Satrio; Yuwono, Akhmad H.; Utomo, Edy P.; Syafrizal, Syafrizal; Imaduddin, Agung (Jurnal Rekayasa Mesin, 2023)
Studying the evolution of the MgB2 superconductor manufacturing process to improve critical temperature is important. The solid-state approach was used in this work to create a low-cost MgB2 superconductor. Variations in the purity of Boron were used as control parameters to evaluate the impact of dry milling on the production of the MgB2 bulk and low-temperature electrical properties. A 2:1 stoichiometric ratio of magnesium and boron powder was weighed and ground for 30 minutes. The ground powder was compressed and sintered for one hour at 1073 K. We were able to confirm through XRD and SEM research that the small particle size improved the MgB2 phase fraction and increase crystallite size in the production of the MgB2 sample. At 1073 K and 200 um of Mg, the sample sintered produced an MgB2 phase of 99.3%. The critical onset temperature (Tc-offset) improved from 39 to 40K, respectively.